2007
DOI: 10.1073/pnas.0610819104
|View full text |Cite
|
Sign up to set email alerts
|

Rho GTPase Cdc42 coordinates hematopoietic stem cell quiescence and niche interaction in the bone marrow

Abstract: Adult hematopoietic stem cells (HSCs) exist in a relatively quiescent state in the bone marrow (BM) microenvironment to fulfill longterm self-renewal and multilineage differentiation functions, an event that is tightly regulated by extrinsic and intrinsic cues. However, the mechanism coordinating the quiescent state of HSCs and their retention in the BM microenvironment remains poorly understood. In a conditional-knockout mouse model, we show that Cdc42 ؊/؊ HSCs enter the active cell cycle, resulting in signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(178 citation statements)
references
References 32 publications
9
164
0
2
Order By: Relevance
“…Yang et al reported that in HSCs from mice conditionally deficient in Cdc42 [30], BM homing, lodging, retention, and long-term repopulation were all impaired. They also showed that Cdc42 signals positively regulate HSC quiescence, suggesting that Cdc42 is essential for physical and functional interaction between HSCs and their niches [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al reported that in HSCs from mice conditionally deficient in Cdc42 [30], BM homing, lodging, retention, and long-term repopulation were all impaired. They also showed that Cdc42 signals positively regulate HSC quiescence, suggesting that Cdc42 is essential for physical and functional interaction between HSCs and their niches [30].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al reported that in HSCs from mice conditionally deficient in Cdc42 [30], BM homing, lodging, retention, and long-term repopulation were all impaired. They also showed that Cdc42 signals positively regulate HSC quiescence, suggesting that Cdc42 is essential for physical and functional interaction between HSCs and their niches [30]. Whether these phenotypes reflect the functions of Cdc42 in normal HSCs remains uncertain, because all mice deficient in Cdc42 die because of progressive myeloproliferative disease [31].…”
Section: Discussionmentioning
confidence: 99%
“…(Morrison et al, 1996;Sudo et al, 2000;Rossi et al, 2005;Waterstrat et al, 2008). Cell intrinsic: genetic factors modify HSC self renewal (Yang et al 2007). The contribution of Cell extrinsic mechanisms is unknown Cell intrinsic: Decline in repopulating capacity on a per cell basis during aging .…”
Section: Cell Intrinsicmentioning
confidence: 99%
“…Disruption of integrin activity in the epidermal and hematopoietic niches resulted in compromised self-renewal (Frye et al, 2003;Scott et al, 2003;Hidalgo et al, 2004;Priestley et al, 2005). There could also be a role in HSC homing and engraftment as a recent report on mice with a targeted cdc42 deletion in hematopoietic cells showed a decrease in ␤1 integrin expression, with excess HSCs throughout the periphery and associated defects of HSC engrafting into bone marrow (Yang et al, 2007). Although it is unclear how integrins regulate stem cell self-renewal, loss of their interaction with the basal lamina may result in loss of integrin-mediated signaling (Hynes, 2002) or alterations in growth factor response (ffrench-Constant and Colognato, 2004) resulting in compromised biological activity.…”
Section: Signaling In Adult Neural and Other Stem Cell Nichesmentioning
confidence: 99%
“…These signaling mechanisms may occur between stem cells, between support cells and stem cells, and between stem cells and differentiating cells. Cell/cell and cell/ECM adhesion and signaling in adult niches is mediated through cell adhesion receptors such as cadherins (Song et al, 2002;Zhang et al, 2003) and integrins (Jones and Watt, 1993;Shinohara et al, 1999;Suzuki et al, 2000;Fujimoto et al, 2002;Frye et al, 2003;Scott et al, 2003;Blanpain et al, 2004;Chen et al, 2004;Deb et al, 2004;Hidalgo et al, 2004;Corbel et al, 2005;Priestley et al, 2005;Wagers and Weissman, 2005;Bajanca et al, 2006;Pajoohesh-Ganji et al, 2006;Lawson et al, 2007;Yang et al, 2007). In this model, as a cell moves away from the niche and thus away from some regulatory signals, it adopts a differentiated phenotype as shown in the pair of cells to the right.…”
Section: Introductionmentioning
confidence: 99%